Key aspects of occupational risks for healthcare workers - N.I. Shulakova; A.V. Tutelyan; V.G. Akimkin (Analiz Riska Zdorovʹû)
At present, the greatest challenge associated with risks in healthcare is the lack of research on occupational diseases associated with healthcare workers’ activities. Despite all achievements of the modern medicine and use of high-tech equipment, occupational health risks remain high in healthcare organizations. Few available literature sources assume that the level of actual occupational morbidity among healthcare workers is considerably higher than the official figures. This does not allow us to fully assess its prevalence. No unified approaches to investigating morbidity among healthcare workers have been developed yet. Analysis of available literature sources has revealed that most studies with their focus on peculiarities of working conditions and health of healthcare workers as well as associated risk factors are rather fragmentary and do not fully encompass all relevant aspects. At present, there is no unified organizational system for occupational safety that includes, among other things, scientific study of the issue. It is advisable to create a concept of occupational health risks in order to provide effective substantiation for selecting managerial decisions on regulation of effects produced by risk factors on personnel employed by healthcare organizations. The methodology for occupational health risk analysis is eligible for becoming an instrument that can ensure an effective policy aimed at protecting and promoting health of healthcare workers.